Synergistic effect of polypyrrole functionalized graphene oxide and zinc phosphate for enhanced anticorrosion performance of epoxy coatings. (March 2020) - Zhu, Qingsong; Li, En; Liu, Xianhu; Song, Weiqiang; Zhao, Mingyang; Zi, Lisen; Wang, Xinchao; Liu, Chuntai
Highlights: It is the first report of polymer functionalized graphene oxide and inorganic salt inhibitors as anti-corrosion pigments. Two mass ratios of polypyrrole functionalized graphene oxide nanocomposites were prepared by in-situ polymerization of pyrrol on the surface of graphene oxide. This work may provide a new direction for further study of compound pigments including functional graphene nanomaterials and inorganic salt inhibitors. Abstract: A promising novel composite coating based on compound pigment of zinc phosphate and polypyrrole (PPy) functionalized graphene (ZGP) was reported for carbon steel in 3.5 wt% NaCl solution. Two ratios of PPy functionalized graphene oxide (GO-PPy) nanocomposites were prepared by in-situ polymerization of pyrrol (Py) on the surface of graphene oxide (GO). PPy film deposited on the surface of graphene oxide guaranteed excellent dispersion in the coating owing to hydrophilic groups. Embedding a small amount of ZGP-2 composite pigment (mPy /mGO = 2:1) into the waterborne epoxy coating significantly improved corrosion protection of the prepared composite coating. The corrosion protection mechanism of the desirable coating was attributed to the synergistic protection of impermeable GO-PPy nanosheets and passivation function of zinc phosphate, which was proved by the identification of corrosion products. Therefore, this work may provide a new direction for further study on compound pigments composed of functional graphene nanomaterials and inorganic salt inhibitors.